Language Assessment Literacy Level of EFL Teachers: A Focus on Writing and Speaking Assessment Knowledge of the Teachers - Hacer Çalışkan; Eda Genç; Assoc. Prof. Doğan Yüksel (Sakarya University Journal of Education)
This study aims to explore Language Assessment Knowledge (LAK) level of high school EFL teachers in terms of assessment of writing and speaking. In addition, another purpose of this study is to investigate whether there is any significant effect of some demographic variables (years of teaching experience, type of undergraduate degree, attending a training course) on teachers’ assessment of writing and speaking knowledge. The previous studies focus on university or primary school context in Turkey; however, there is no study which gave place to the high school context. The study was conducted among 58 high school EFL teachers in Turkey. A demographic questionnaire with 8 questions was used for collecting certain demographic information about the teachers. Language Assessment Knowledge Scale (LAKS) which is comprised of 30 items and 2 dimensions (writing and speaking) was used for gathering the data. The data was analysed through Two-Way Multivariate Analysis of Variance (MANOVA). The results demonstrated that the teachers have high literacy knowledge in one of the sub-component fields while they have low literacy knowledge in the other field.